Branching and rheological behavior after electron irradiation in metallocene ethylene-co-norbornene copolymers - Cerrada, María L. (2011)
The effect of Electron beam (EB) irradiation on a cycloolefin copolymer based on ethylene and norbornene with intermediate molar content of norbornene has been evaluated. Crosslinking is not observed at any dose analyzed. Scission and branching of the chains simultaneously occur at low and high irradiation doses. Scission prevails for doses up to 167 kGy and, then, branching becomes dominant in the rheological bulk response at the highest dose. These side chains favor the development of reversible physical networks through entanglements and, accordingly, the GN 0 value and the dynamic and zero-shear viscosities increase at high levels of irradiation compared with the same parameters found at smaller EB doses. The resulting structures attained after irradiation at different doses are inactivated to microorganism development and exhibit higher thermal stability and a broader temperature window for its standard applications in comparison with the pristine non-irradiated ethylene-co-norbornene (EN) copolymer.